Solve the simultaneous equations: y-2x-4 = 0 (1) , 4x^2 +y^2 + 20x = 0 (2)

Re-arrange (1) : y = 2x + 4 Square both sides: y^2 = 4x^2 + 16 Substitute (1) into (2) and simplify: 2x^2 + 9x + 4 = 0 Factorise the equation: (2x+1)(x+4) = 0 Solve for x: x = -1/2 and x = -4 Substitute these x values in (1) to find corresponding y values for each x.

Answered by Giorgos A. Maths tutor

9052 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How do you find the gradient of a line?


Express cos(2x) in terms of acos^2(x) + b


How do I use the chain rule for differentiation?


Find the inverse of the matrix C=(1,2;4,9)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences